Genome-Wide Identification and Functional Analyses of the CRK Gene Family in Cotton Reveals GbCRK18 Confers Verticillium Wilt Resistance in Gossypium barbadense - Li, Ting-Gang; Zhang, Dan-Dan; Zhou, Lei; Kong, Zhi-Qiang; Hussaini, Adamu S.; Wang, Dan; Li, Jun-Jiao; Short, Dylan P. G.; Dhar, Nikhilesh; Klosterman, Steven J.; Wang, Bao-Li; Yin, Chun-Mei; et al. (Frontiers in Plant Science, 2018)
Cysteine-rich receptor-like kinases (CRKs) are a large subfamily of plant RLKs that play a critical role in disease resistance in plants. However, knowledge about the CRK gene family in cotton and its function against Verticillium wilt, a destructive disease caused by Verticillium dahliae that significantly reduces cotton yields, is lacking. In this study, we identified a total of 30 typical CRKs in a Gossypium barbadense genome (GbCRKs). Eleven of these (> 30%) are located on the A06 and D06 chromosomes, and 18 consisted of nine paralogous pairs encoded in the A and D subgenomes. Phylogenetic analysis showed that the GbCRKs could be classified into four broad groups, the expansion of which has probably been driven by tandem duplication. Gene expression profiling of the GbCRKs in resistant and susceptible cotton cultivars revealed that a phylogenetic cluster of nine of the GbCRK genes were up-regulated in response to V. dahliae infection. Virus-induced gene silencing of each of these nine GbCRKs independently revealed that the silencing of GbCRK18 was sufficient to compromise Verticillium wilt resistance in G. barbadense . GbCRK18 expression could be induced by V. dahliae infection or jasmonic acid, and displayed plasma localization. Therefore, our expression analyses indicated that the CRK gene family plays a role in defense responses, while silencing experiments revealed that GbCRK18 in particular confers Verticillium wilt resistance in G. barbadense.